The Leipzig Health Atlas—An Open Platform to Present, Archive, and Share Biomedical Data, Analyses, and Models Online - Kirsten, Toralf; Meineke, Frank A.; Loeffler-Wirth, Henry; Beger, Christoph; Uciteli, Alexandr; Stäubert, Sebastian; Löbe, Matthias; Hänsel, René; Rauscher, Franziska G.; Schuster, Judith; Peschel, Thomas; Herre, Heinrich; Wagner, Jonas; Zachariae, Silke; Engel, Christoph; Scholz, Markus; Rahm, Erhard; Binder, Hans; Loeffler, Markus; on behalf of the LHA team (Methods of Information in Medicine, 2022)
Background Clinical trials, epidemiological studies, clinical registries, and other prospective research projects, together with patient care services, are main sources of data in the medical research domain. They serve often as a basis for secondary research in evidence-based medicine, prediction models for disease, and its progression. This data are often neither sufficiently described nor accessible. Related models are often not accessible as a functional program tool for interested users from the health care and biomedical domains.Objective The interdisciplinary project Leipzig Health Atlas (LHA) was developed to close this gap. LHA is an online platform that serves as a sustainable archive providing medical data, metadata, models, and novel phenotypes from clinical trials, epidemiological studies, and other medical research projects.Methods Data, models, and phenotypes are described by semantically rich metadata. The platform prefers to share data and models presented in original publications but is also open for nonpublished data. LHA provides and associates unique permanent identifiers for each dataset and model. Hence, the platform can be used to share prepared, quality-assured datasets and models while they are referenced in publications. All managed data, models, and phenotypes in LHA follow the FAIR principles, with public availability or restricted access for specific user groups.Results The LHA platform is in productive mode (https://www.health-atlas.de/). It is already used by a variety of clinical trial and research groups and is becoming increasingly popular also in the biomedical community. LHA is an integral part of the forthcoming initiative building a national research data infrastructure for health in Germany.
Keywords: FAIR; data semantics; research data management; metadata; clinical trials; biomathematical models; ontology; risk prediction models; omics data